The Effect of Service and Profit Sharing on the Interests of Non-Muslim Customer to be Customer of Sharia Bank (Case Study At BRI Syariah KC (Branch Office) Manado) - Nur Atika Thayeb (Tasharruf: Journal Economics and Business of Islam, 2019)
Abstract:This study aims to find the effect of Service and Profit Sharing on Non-Muslim Customer Interests to Become Customers in BRI Syariah Manado. The main problem is how much the influence of the Service and Profit Sharing toward the Interests of Non-Muslim to Become Customers in BRI Syariah Manado. The type of research used is quantitative research. The population in this study were non-Muslim customersof BRI Syariah Manado.Data analysis techniques in this study are validity test, reliability test, normality test, multicollinearity test, autocorrelation test, heteroscedasticity test, multiple regression test, F test and T test.The results of this study conclude that the Regression Coefficient X1 (service) is 0.336 (33.6), service is a factor that affects the interest of non-Muslim to become customers of the BRI Branch KC (Branch Office) Manado, and the Regression Coefficient X2 (Profit Sharing) amounting to 0.410 (41.0), stating that the Profit Sharing variable has a positive influence and the most influential factor on the interest of non-Muslim to become BRI Syariah Manado customers. based on the results of these studies, it conclude that the better the Bank Sharing Profit, the better the interest of non-Muslim customers to become customers. Furthermore, it is recommended for the BRI Syariah KC (Branch Office) Manado to further improve the quality of services so that the non-Muslim community is more interested in becoming a customer at the Manado KC (Branch Office) BRI and for Profit Sharing should be more concerned by the bank, so that non-Muslims are more familiar with Profit Sharing Products.Keyword: service, Profit sharing, interest.